Pencegahan Kekerasan Dalam Rumah Tangga Berbasis Penegakan Hukum Dan Falsafah Budaya Jawa Mbangun Kromo Di Kulon Progo - Acita, Fonni; Ismail, Bayu; Sukmaningsih, Juwita; Alfatiha, Inaya; Oktavian, Diky; Khakim, Mufti (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Domestic Violence (KDRT) is an iceberg phenomenon, where what is visible is less than what is not visible. One of the characteristics of domestic violence is domestic violence, this is what makes this act of violence so little can be revealed. This research aims to provide a solution in preventing criminal acts of domestic violence using a law enforcement approach, namely a Javanese cultural approach. The special relationship between the perpetrator and the victim is that they are part of the family and violence is often considered a family disgrace so that they cover each other up. The legal approach is less effective in preventing and overcoming it due to the lack of public awareness that domestic violence is a serious global crime. Therefore, a cultural approach needs to be pursued, namely the role of Javanese philosophy in the lives of Javanese people to prevent domestic violence. This type of research is empirical normative research using an ethnographic approach. Primary data with direct interviews with research subjects regarding Javanese philosophy. The results of this research are a description of the Javanese community in Triharjo Village in implementing the Javanese philosophy of Mbangun Kromo and the effectiveness of the Javanese Mbangun Kromo philosophy in preventing domestic violence. The conclusion from this research is that preventing domestic violence using a cultural approach is quite effective in preventing the occurrence of domestic violence. Keywords: Javanese philosophy; violence; household